Pediatric Robotic Surgery : Technical and Management Aspects - Mattioli, Girolamo; Petralia, Paolo (Springer International Publishing : Imprint: Springer, 2017)
This book presents the state of the art across the entire field of pediatric robotic surgery, including thoracic, abdominal, oncologic, gynecologic, and urologic procedures. Indications for each type of robotic surgery are clearly set out and technical aspects are described in detail, illustrating the patient's position and explaining the robotic assessment and the optimal use of robotic instruments. Anesthetic issues and the management of robotic complications are discussed, and managerial aspects are also considered, with provision of helpful suggestions on how to approach robotic surgery in each pediatric department. For surgeons who wish to start using the pediatric robotic approach, simple illustrations of robotic assessment and principles of robotic surgery are included. Pediatric robotic surgery has undergone significant development in recent years, and the technology is now applied to a variety of pediatric diseases beyond urology. This book has been written by a group of world-renowned pioneers of pediatric robotic surgery and will appeal to pediatric surgeons of all disciplines, to residents, and to hospital general managers and medical directors.